2019
DOI: 10.1371/journal.pone.0226742
|View full text |Cite
|
Sign up to set email alerts
|

Clinical nurses’ beliefs, knowledge, organizational readiness and level of implementation of evidence-based practice: The first step to creating an evidence-based practice culture

Abstract: BackgroundThis study aimed to identify clinical nurses’ evidence-based practice (EBP) knowledge, beliefs, organizational readiness, and EBP implementation levels, and to determine the factors that affect EBP implementation in order to successfully establish EBP. This study was conducted at a university-affiliated tertiary hospital located in a provincial area in Korea. The research design was based on Melnyk and Fineout-Overholt’s Advancing Research & Clinical Practice through Close Collaboration model as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
68
0
14

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(105 citation statements)
references
References 38 publications
9
68
0
14
Order By: Relevance
“…Similarly, engagement, which falls under the process domain, and the characteristics of individuals domain consider an array of inner and outer setting individuals. Though the characteristics of individuals constructs were discussed minimally in the surveys, prior studies have demonstrated that they are closely related to culture and engagement and together can in uence implementation (13,14). discrimination (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, engagement, which falls under the process domain, and the characteristics of individuals domain consider an array of inner and outer setting individuals. Though the characteristics of individuals constructs were discussed minimally in the surveys, prior studies have demonstrated that they are closely related to culture and engagement and together can in uence implementation (13,14). discrimination (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, engagement, which falls under the process domain, and the characteristics of individuals domain consider an array of inner and outer setting individuals. Though the characteristics of individuals constructs were discussed minimally in the surveys, prior studies have demonstrated that they are closely related to culture and engagement and together can in uence implementation (13,14). Less trans-a rming attitudes and actions within healthcare networks is usually attributed to a lack of education and training regarding transgender people, their healthcare disparities and their speci c healthcare needs.…”
Section: Discussionmentioning
confidence: 99%
“…The level of nurses' confidence in the importance of evidence-based practice becomes a positive value in implementing, this from several studies conducted in various countries such as Korea, China, Greece, Iraq, Oman, and Singapore (Majid et al , 2011;Khammarnia et al, 2015;Patelarou et al, 2016;Al-Busaidi et al, 2019;Chen et al, 2019;Yoo et al, 2019) suggested that nurses' confidence in EBP was quite high. In this series of studies, it clearly showed the nurse population alone so that data showing nurses' belief in EBP in high significant values but research conducted in Taiwan by looking at EBP confidence comparisons on the multi profession.…”
Section: Implementation Of Ebp Nurses On An Individual Levelmentioning
confidence: 99%
“…Two different studies conducted in South Korea (Park and Jang, 2016;Yoo et al, 2019) showed that there positively increased in EBP on the knowledge/ skills of EBP of Korean nurses. In contrast to research conducted in Greece (Patelarou et al, 2016) reported that half of the nurses said they were not sure of their ability to be involved in EBP.…”
Section: Implementation Of Ebp Nurses On An Individual Levelmentioning
confidence: 99%